Generic Models of Willow (genus Salix L.) Tree Phytomass: a Meta-Analysis - Andrey А. Paramonov; Vladimir A. Usoltsev; Sergey V. Tretyakov; Ilya V. Tsvetkov; Ivan S. Tsepordey (Лесной журнал)
Climate change has a negative impact on the environment, including forest ecosystems. However, forests are not only passive objects affected by climate change, but also, due to their ability to absorb and accumulate carbon, they themselves can significantly influence this process. Carbon sequestration by forest ecosystems plays an important role in mitigating the effects of climate change. Therefore, it is necessary to know about the amount of carbon stored in forest phytomass, and it is becoming increasingly important to accurately determine the phytomass of forest trees. Due to the absorption of carbon dioxide during plant growth and its release during wood burning, forests are a carbon-neutral energy source. The idea of using phytomass as an energy source to replace fossil fuels is most promising for fast-growing species. These include willows (genus Salix L.), native to Europe, Asia, America and Africa and found from the tundra to the tropics. Willow is successfully used as fuel in many countries, showing excellent growth and productivity even at juvenile stages and, under certain climatic conditions, having the highest capacity among woody plants to convert solar radiation into phytomass. Short-rotation willow plantations represent an ecologically promising energy resource for reducing greenhouse gas levels. Since the development of phytomass models is a laborious process, so-called “generic meta-models” are used. The aim of this study has been to construct generic models of both aboveground phytomass and phytomass fractions (foliage, branches, stem, roots) of willow trees based on meta-analysis of data. In the course of the work, the models have been constructed for assessing the aboveground phytomass of trees both in diameter at the stem base and in diameter at breast height, the information content of which is close to functional, and the biases are only about 2 %. Since each fraction of phytomass has a specific carbon-sequestering capacity and makes a different contribution to the carbon balance, generic models have been developed to estimate the mass of foliage, branches, stems and roots in relation to the aboveground phytomass of trees, explaining from 82 % (for foliage) to 99 % (for stems and roots) of the total variability of phytomass.